Determinants of compliance to occupational safety and health standards in food manufacturing industries, Thika Sub-County, Kiambu County, Kenya - Njoroge, Teresiah W.; Odongo, Alfred O.; Muchiri, Joseph M. (International Journal Of Community Medicine And Public Health, 2025)
Background: It is mandatory for all workplaces to prioritize the safety and health of their employees by adhering to OSH rules and regulations to prevent work-related illnesses, accidents, injuries, and fatalities. The study aimed to assess the determinants of compliance with occupational safety and health standards among employees in food manufacturing industries in Thika sub-county, Kiambu County, Kenya. Methods: The research used an analytical cross-sectional study design. Stratified sampling techniques were utilized to select study respondents for this research. The chi-square test was used for bivariate analysis, and Binary logistic regression was also applied for determinants found to be significant in bivariate analysis. The cutoff for statistical significance was p<0.05. Qualitative data was analyzed thematically. Results: From this study, the compliance rate to occupational safety and health standards was 76.5%. the provision of PPEs (OR=2, 95%CI=0.29-0.96), having a working experience of 1-4 years (OR=5.9, 95%CI=0.06-0.49) increased the odds of complying with occupational safety and health standards while being a male (OR=2.1, 95%CI=1.12-3.92) and having a primary level of education (OR=8.3%, 95%CI=2.28-30.53) reduced the odds of complying with occupational safety and health standards. Conclusions: The compliance rate with occupational safety and health standards was 76.5%. From this study, the provision of PPEs, and having a working experience of 1-4 years increased the odds of complying with occupational safety and health standards while being a male and having a primary level of education reduced the odds of complying with occupational safety and health standards.